"Obok. Polska – Niemcy. 1000 lat historii w sztuce" jako przykład wystawy politycznej - Lorenc, Magdalena (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2013)
The objective of the paper is to analyze and assess the institutional conditions of the exhibition entitled Side by Side. Poland – Germany. 1000 years of Art and History, organized in Martin-Gropius-Bau in Berlin between September 23, 2011 and January 9, 2012. In terms of the number of works of art presented this undertaking was unprecedented in the history of Polish-German relations. The exhibition, and the catalogue that accompanied it, were a part of the Cultural Program of the Polish Presidency in the EU Council in 2011, becoming an exemplification of the issue of the politicization of exhibition discourse, where works of art are utilized for political purposes. The theoretical inspiration for considering this topic was provided by Peter Vergo’s concept presented in his text The reticent object of 1987. In Vergo’s opinion, exhibitions are a cultural fact which is relatively rarely investigated in terms of the means, efforts, conditions and reasons that are necessary for their execution. And yet these institutional conditions, including their financing, the procedures for selecting the entities in charge of the project, the mechanisms for appoint the program board and honorary patronage have a considerable influence on the nature of the exhibition. Concentrating on institutional contexts serves the purpose of answering the question of how the realms of politics and art exhibitions permeate one another. The decisions made by the authorities to become involved in certain exhibition projects constitute the instruments for creating and executing selected public policies, primarily cultural policy. It is therefore impossible to assess the success of a given initiative without considering the political objectives set and achieved by the organizers of the exhibition Side by Side.
Side by Side. Poland – Germany. 1000 years of Art and History as an example of a political exhibition
Keywords: historia; sztuka; wystawa polityczna; stosunki polsko-niemieckie